Gestão e organização para a conversão do conhecimento: processos de apoio para decisões estratégicas - Rogério Amaral Bonatti (2020)
The research question on the decision-making process of the energy sector was defined with the feasibility of a research project established between Escola de Ciência da Informação da Universidade Federal de Minas Gerais and Companhia Energética de Minas Gerais S.A., and had the support of the Fundação de Desenvolvimento da Pesquisa. The research project proposal was to provide information management to foster the sustainability of the electricity generation portfolio in the concessionaire's energy matrix in the national scenario. As the main objective of this work, seek, through the management and organization of knowledge, to provide improvements in the strategic decision-making process. For this, undertaking not to obtain an effect of effecting the conversion of knowledge activated in the explicit and obtaining elements that influence these decisions. Therefore, from the perspective of an energy utility, the study sought to map and understand the decisive process in investments in alternative renewable sources. The generation activity was widely disseminated among organizations and many countries turn to less polluting options that have less impact on the environment. The identification and survey of parameters in the decision-making process were carried out in this context. Initially, it was necessary to list the main information resources used by utilities, such as scientific publications and specific regulations in the energy sector. The development and validation of terms that represent the measurement of knowledge and the relevance of the topic for new solutions to the growing demand for electricity generation are the main expected contributions. Interviews and questionnaires provide information that, when analyzed, provided help to define the current investment interests of these concessionaires. It was made a proposal to use non-measurable parameters to define an option that represents the opinions of managers in an investment opportunity. For this, it is used a multicriteria method,wich studies have shown its applicability to problems of the same nature and use. Thus, the objective of this study was to demonstrate the applicability of concepts and techniques applicable to the management and organization of knowledge to assist in the strategic decision-making process. We proceeded to demonstrate by a practical experiment for the conversion of activated knowledge into the explicit and thus obtain elements inherent to strategic decisions in the specific context of the generation of electric energy. Actions were taken to involve various sectors and participation groups. It is expected that the demonstration of the processes used and the application of this resource on that research can contribute to the delimitation of contexts in several areas of application.